Programs of the preventive interventions against sexually transmitted infections in the high-risk subpopulations - T. V. Krasnoselskikh; E. V. Sokolovskiy (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
A review article highlights the practical issues of design, implementation and effectiveness estimation of STI prevention programs aimed to correct the behavior leading to infection. the importance of epidemiological modeling method for the organization of preventive interventions is discussed. the prospects of the multidisciplinary behavioral approach to STI prevention are demonstrated.